Does call centers operators’ introjected regulation impact their skill variety and task significance? Evidence from Morocco - Belhaj Soulami, Marwa; Loulidi, Sofia (Business, Management and Economics Engineering, 2024)
Purpose – The aim of this paper was to empirically examine the impact of work motivation represented by introjected regulation on job satisfaction, which was illustrated by skill variety and task significance. This study was conducted relatedly to Moroccan call center operators, in the post-COVID-19 era in which motivational and satisfactory issues are still strongly faced by managers, mainly due to the operated hybrid working systems.Research methodology – The chosen methodology was a quantitative one, based on the administration of a questionnaire to 158 call center operators, working in various Moroccan districts. The data analysis consisted of an exploratory factor analysis (EFA), followed by a full structural equation modelling (SEM).Findings – The findings display that introjected regulation positively and significatively impacts skill variety, but not task significance, in a way that permitted to partly confirm the conceptual model built upon the central hypothesis, claiming that work motivation positively affects job satisfaction. Indeed, avoiding to experience feelings of shame and guilt in addition to seeking for conformity and approbation in a work context turned out to lead individuals to execute the assigned tasks by implementing their personal configuration of skills and talents in this regard.Research limitations – This study admits methodological limitations as for instance the restricted sample size, and the adopted quantitative approach rather than a qualitative one, or even a mixed approach that could have opened more research tracks to be explored regarding the investigated relationship.Practical implications – This study comes out with appealing practical implications willing to help managers to understand better the causality link between work motivation and job satisfaction. The main implication of this study is the illustration of how introjected regulation can predict and foster skill variety in a professional context, as the correspondent research hypothesis was empirically verified.Originality/Value – Morocco is admittedly one of the poorest targeted populations for International Business and Management studies, hopefully this study can contribute in enriching the pre-existent studies in this regard. Also, work motivation and job satisfaction are usually seen as qualitative variables (using interviews, case studies…), hence a quantitative methodology is not commonly adopted in this perspective.